Loyalty Retention Strategy Through After-Sales Service at Honda Car Dealers in Pekanbaru City - Trisningkasih Fitriastuti; Zulkarnain; Raden Lestari Ganarsih (Universitas Airlangga, 2026)
Background: After-market services are often overshadowed by the significant attention given to pre-sale marketing strategies. In developing economies, such as Indonesia, the lack of after-market service support leads to dwindling repeat purchases and a loss of brand loyalty. The phenomenon underscores the need to evaluate how post-purchase service provision affects long-term customer retention within the automotive industry. Objective: This study aims to identify the direct effect of post-purchase support services on customer loyalty, and to examine the correlations through other potential mediating factors with dual mediation of brand equity and customer satisfaction. This research also attempts to measure the extent to which service-related experience is manifested in the emotional and behavioural aspects of loyalty. Method: A quantitative explanatory design was utilised, with primary data collected from a sample of 105 customers who have had at least two paid service visits at an authorised Honda dealership in Pekanbaru. Using the SEM framework and the Partial Least Squares estimation technique, we can analyse multiple interrelated cause-and-effect relationships. Results: The results demonstrate a substantial positive relationship between post-purchase service quality and customer loyalty (β = 0.53, p < 0.01), alongside significant positive indirect effects via brand equity (β = 0.35) and customer satisfaction (β = 0.29). The existence of positive dual mediating effects indicates that the sustained loyalty intentions construct, service quality perceptions, and emotional attachment to the brand are positively dual-mediating. Conclusion: This study advances the understanding of service-based loyalty mechanisms by empirically validating the strategic leverage of after-sales service in emerging markets. The insights offer actionable guidance for automotive dealership managers to reframe service departments from cost centres into high-impact drivers of customer retention and competitive differentiation. Keywords: After Sales Service; Brand Equity; Customer Satisfaction; Customer Loyalty